Ragam Bahasa Santai dalam Tuturan Ilokusioner pada Kegiatan Diskusi Publik Sinau Kedaulatan dan Kebudayaan Bersama Cak Nun - lulu, Talitha; Gigit Mujianto (GERAM: Gerakan Aktif Menulis, 2021)
The study was intended to analyze the casual language variations in the iloquestionnaire's speechs on the public discussion activities. This study uses sociolinguistics concepts from John R Searle’s theory to analyze the problems of casual language variations and any form of iloquestionnaire's speechs. This study is a qualitative descriptive research. The data collection technique that used is purposive sampling method, which in taking samples is concerned with the purpose and problems of research. Data obtained by using transcription videos of “diskusi publik kedaulatan dan kebudayaan bersama cak Nun”. This study uses data analysis techniques in the form of content analysis. The data analysis techniques are as follows: 1) looking back over the data already collected, 2) classifying the data according to the question of variations in casual language and iloquestionnaire's speech, 3) interpreting the data with a sociolinguistic approach and John R Searle's theory, and 4) concluding the findings. Studies showed that discussion activities use a variety of casual language with characteristic Javanese, Alegro forms, elliptic sentences, and a mixture of the foreign language code, English and Arabic, and Normative. In the discussion activities, there are various forms of iloquconsequence, referral, commission, expressive, and declarative